The Relationship Between the Financial Innovation and the Money Supply: Empirical Study on the Maghreb Countries - Djaballah, Mustapha (Economics and Business, 2020)
This article examines the relationship between money supply and financial innovation in the Maghreb countries over the period of 1980–2018 for a large annual data set on five Maghreb countries using the panel autoregressive distributed lag model (PANEL-ARDL). The results obtained from the cointegration technique of Pesaran and Shin (1999) confirm that a long-term relationship exists between M2 and its determinants: GDP, inflation, and the credit interest rate. Above all, the results of the research show that mobile money positively and significantly influences the money supply both in the strict sense and in the broad sense. Also, the number of ATMs positively but not significantly influences the supply of money in the broad sense. Failure to take into account the expansion of the number of ATMs can therefore lead to a poor specification of the money supply, and monetary authorities need to explicitly integrate the effect of financial innovation for effective policy action to stabilize economies.